Engaging customers through online and offline referral reward programs. (9th September 2019) - Wirtz, Jochen; Orsingher, Chiara; Cho, Hichang
Abstract : Purpose: This paper aims to examine the psychological consequences of a customer engagement initiative through referral reward programs (RRPs) in online versus offline environments. Design/methodology/approach: The authors conducted a qualitative study followed by a scenario-based experimental study. Findings: The authors show that recommenders' concern about how they are viewed by recommendation recipients (i.e. their metaperception) mediates the effects of incentives on referral likelihood in both offline and online environments. However, metaperception has a stronger effect offline where recommenders show higher impression management concerns compared to online. Furthermore, tie-strength and communication environment moderate the effect of incentives on metaperception. When referrals are made to weak-ties, incentives decrease metaperception favorability offline more than online. For strong-ties, this effect is lower, and it is similar in offline and online environments. Research limitations/implications: The study focused on an online versus offline dyadic communication and did not consider the differences among social media. Furthermore, the authors did not consider how other forms of positive metaperception, like being seen as helpful or knowledgeable, could be increased in an online incentivized referral context. It is possible that a recommender thinks others see him as more helpful or knowledgeable online because a lot more useful information and other resources could be offered here compared to offline communications. Practical implications: The authors recommend managers to design both online and offline RRPs that minimize metaperception concerns; target strong ties in any communication environment as metaperception concerns are low; and target weak ties online where metaperception concerns are muted. Originality/value: This work is the first to examine how recommenders' psychological responses differ offline and online.